Problematics Of Using Learning Media In Fiqih Subjects To Create Effective Learning In MAN Sidikalang - Munthe, Debi Rezi; Pardosi, Rabba Yeni; Berutu, Rolli (-, 2024)
The aim of this research is to look at the problems of using learning media in Fiqih subjects at MAN Sidikalang. This research was conducted qualitatively using a case study approach. Data was collected through observation, thorough interviews with fiqih teachers, and questionnaires distributed to students. The research results show that some of the main obstacles in using learning media at MAN Sidikalang are limited access to technology, lack of instructions for teachers on how to use learning media, and lack of school support. In addition, it was found that when learning media is used and is relevant to students' daily lives, they tend to be more interested and motivated. And furthermore, the research results show that there are several ways to overcome current problems, such as improving school technology facilities, providing intensive training to teachers on how to use learning media, and developing learning media that are more innovative and appropriate to students' local context. By implementing these strategies, it is hoped that Fiqih learning at MAN Sidikalang will become more effective.